2011
DOI: 10.1007/s10508-011-9821-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism and Personality Attributions of Male Faces

Abstract: Individuals tend to judge personality traits on the basis of physical characteristics, particularly facial traits, although this phenomenon has been mostly studied in relation to the halo effect of attractiveness. However, there are other facial traits which may also have an impact on personality attributions; here, we focused on masculinity. We carried out principal component analysis (PCA) of 15 anthropometric measurements from 71 male faces, resulting in three components: Face Height (C1), Inner Face Breadt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The attractiveness cluster seemingly represents the halo effect (the hypothesis stating that attractive people are evaluated more positively regarding positively loaded personality traits [28], [29]): High scores for Attractive clustered with high scores for Extraverted, Emotionally Stable, Physically Healthy, and Adventurous. We further discovered a clear link between scores for Dominating and Masculine for men (r(114) = .73, p<.001), which was in agreement with previous results [14], [30]. We compared the Ratings between genders with a Welsh's t-test and found that women generally are perceived as more trustworthy (p = 3.19×10 −5 ), responsible (p = 4.40×10 −10 ) and attractive (p = 6.35×10 −9 ), whereas men are seen as more emotionally stable (p = 4.04×10 −6 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The attractiveness cluster seemingly represents the halo effect (the hypothesis stating that attractive people are evaluated more positively regarding positively loaded personality traits [28], [29]): High scores for Attractive clustered with high scores for Extraverted, Emotionally Stable, Physically Healthy, and Adventurous. We further discovered a clear link between scores for Dominating and Masculine for men (r(114) = .73, p<.001), which was in agreement with previous results [14], [30]. We compared the Ratings between genders with a Welsh's t-test and found that women generally are perceived as more trustworthy (p = 3.19×10 −5 ), responsible (p = 4.40×10 −10 ) and attractive (p = 6.35×10 −9 ), whereas men are seen as more emotionally stable (p = 4.04×10 −6 ).…”
Section: Resultssupporting
confidence: 92%
“…On one hand, there is some truth behind first impressions - it has been shown that valid inferences are made for at least four personality traits (Agreeableness, Conscientiousness, Extraversion, and Dominance) from facial features [10][13] - on the other hand, first impressions are not always accurate, e.g. people with infant-like facial traits (small chin, high eyebrows, and large eyes) are perceived as more emotionally warm, submissive, and naive [14], but often the direct opposite is true, as seen in many adolescent boys [15]. One cause of these inaccuracies is that people generate trait evaluations based on neutral facial expressions resembling actual emotional expressions – an effect named the overgeneralisation hypothesis [16].…”
Section: Introductionmentioning
confidence: 99%
“…These results were largely consistent when exploring the relationship by gender of rater. Previous research has suggested similar results in face [72] and voice perception [68], [73], with findings pointing to increased attractiveness as masculinity/strength increases in males and as friendliness/warmth increases in females.…”
Section: Discussionsupporting
confidence: 62%
“…The portraits were taken with a Canon 350D camera with the focus Canon EF 50/1.8 II from a distance of 1.5 m. A light blue background was used to optimise white balance, following digital adjustments. In order to eliminate possible influences of hairstyle, only faces with scalps covered were used for the ratings (procedure used in previous studies, eg Pivonkova et al 2011). The scalps were covered using Photoshop 7.0 software, and faces were placed on a black background.…”
Section: Facial Photographsmentioning
confidence: 99%